Genetic manipulation of self-incompatibility in diploid potato species - Dzidzienyo, Daniel Kwadjo (2013)
Many of the wild and some cultivated species of potato are true diploids and are therefore more amenable for genetic studies than the majority of tetraploid cultivars. However, the use of these diploid Solanum species is complicated by almost universal self-incompatibility (SI). In Solanum, SI is gametophytic and pistil specificity is controlled by a polymorphic ribonuclease (S-RNase), as found in other members of the Solanaceae. The genetic engineering of self-compatible (SC) diploid potato lines would benefit potato breeding in general and allow inbred lines to be established for the first time. This would facilitate genetic analyses including that of complex traits such as drought resistance or yield. The aim of this thesis is to down regulate the expression of S-RNases in diploid potatoes using the RNAi technique and established procedures for Agrobacterium-mediated transformation. This approach to engineering self-compatibility has already been successfully demonstrated in SI Petunia inflata (Lee et al., 1994) and other species of the Solanaceae. To date just a handful of S-RNase sequences are available for potato species. The characterization of S-RNases in targeted diploid Solanum species was an initial requirement for our approach. To develop the tools, S-alleles have initially been characterized in both Petunia inflata and P. hybrida cv Mitchell both phenotypically (by pollination tests using a diallel cross) and/or genotypically (by RT-PCR). This approach was then transferred to three diploid potato species, specifically accessions of Solanum stenotomum, Solanum phureja and Solanum okadae. These wild species are important sources of new traits studied by The James Hutton Institute (formally the Scottish Crop Research Institute). The approach taken to amplify partialS-RNase sequences from pistil RNA was RT-PCR using a degenerate primer. PCR products were cloned using a TA vector (Invitrogen) and sequenced. For two alleles full length sequences were obtained by 5'RACE. Database searches with these sequences, revealed sixteen S-RNases several of which are novel. Phylogenetic analYSis was carried out with the cloned S-RNases together with selected published S-RNase and S-like RNase sequences of solanaceous species. The S-RNases revealed extensive trans-generic evolution and are clearly distinct from and distantly related to S-like RNases. For two alleles (501 and 502), S-RNase gene expression profiling was performed to check the developmental expression of the S-RNase gene, tissue-specific expression and also test whether these S-RNases (e.g. Sor and S02-RNases) are expressed at a similar level. Wide variation in S-RNase gene expression levels have been reported in the literature. An RNAi construct has been designed to down-regulate two specific 5-RNases in an 501/502 heterozygote of S. okadae. To increase the chance of Silencing, the RNAi construct has been designed to use a chimeric 5-RNase gene involving the 5' end of the SorRNase and the 3' end of the S02-RNase. The correct chimeric S-RNase construct (SOl/S02-RNase) has now been identified and inserted into an RNAi vector (pHelisgate8) using Gateway® technology. This RNAi construct (pHG8-S01/S02) is now a valuable resource for use in S-RNase gene silencing in potato leading to the development of self-compatible diploid potato lines and ultimately the development of the first inbred lines of S. okadae.